18.0% efficiency flexible perovskite solar cells based on double hole transport layers and CH3NH3PbI3−xClx with dual additives. Issue 32 (3rd August 2018) - Hou, Lixin; Wang, Yali; Liu, Xianhao; Wang, Jia; Wang, Lixin; Li, Xiaowei; Fu, Guangsheng; Yang, Shaopeng
Abstract : The performance of flexible perovskite solar cells (PSCs) is largely lower than that of their glass/ITO counterparts. Abstract : The performance of flexible perovskite solar cells (PSCs) is largely lower than that of their glass/ITO counterparts. This is mainly due to the fact that the surface of PET/ITO is rougher than glass/ITO. ITO bulges could cause the upper perovskite crystals to deteriorate, eventually leading to a large leakage current and the low performance of devices. We reduce the leakage current of PET/ITO assembled PSCs by two measures to improve the PCE of the flexible PSCs. First, double hole transport layers of PEDOT:PSS/NiO are deposited on the surface of PET/ITO, that is, a layer of PEDOT:PSS film is first spin-coated on the ITO surface and then a layer of NiO film is evaporated above to cover the small bulges on the bare ITO. Second, the dual additives of DIO and H2 O were introduced to the perovskite precursor solution to control the process of crystal formation and grain growth of the perovskite absorber, finally improving the uniformity and sizes of the perovskite crystals. In conclusion, the double hole transport layers and CH3 NH3 PbI3− x Cl x perovskites with dual additives produced a perovskite film with low roughness, high uniformity and large crystal grains on PET/ITO, finally achieving flexible PSCs with the best PCE of 18.0% and excellent flexibility. Our approach provides an effective pathway to fabricate highly efficient and large-scale flexible PSCs.